Mammary analog secretory carcinoma of the parotid gland: A case report and literature review. (2015) - Balanzá, Ricardo; Arrangoiz, Rodrigo; Cordera, Fernando; Muñoz, Manuel; Luque-de-León, Enrique; Moreno, Eduardo; Toledo, Carlos; González, Edgar
Highlights: Mammary analog secretory carcinoma (MASC) is a newly described carcinoma of the salivary glands. MASC is characterized by morphologic and immunohistochemical features that strongly resemble a secretory carcinoma (SC) of the breast. MASC and SC of the breast share the presence of translocation t(12;15) (p13;q25), that results in the formation of an oncogenic fusion gene ETV6-NTK3. The majority of MASC present among men and arise from the parotid gland. MASC is a low-grade carcinoma with potential for high-grade transformation. Abstract: Background: Mammary analog secretory carcinoma (MASC) was first described in 2010 by Skálová et al. This entity shares morphologic and immunohistochemical features with the secretory carcinoma (SC) of the breast. MASC usually presents as an asymptomatic mass in the parotid gland and predominantly affects men. This tumor is considered a low-grade carcinoma but has the potential for high-grade transformation. We report one MASC case and a review of world literature. Case report: A 66-year-old male patient presented because he noticed a mass of approximately 3 × 3 cm on the right pre-auricular region. Physical examination demonstrated a 3 × 3.5 cm, firm, fixed, non-tender mass in the right pre-auricular region. An MRI of the head and neck showed an ovoid heterogeneous lesion, dependent of the right parotid gland of 27 × 28 mm. We performed a superficial parotidectomy with identification and preservation of the facial nerve. The immunophenotype was positive for epithelial membrane antigen (EMA), CK8/18, vimentin, S-100 protein, and mammoglobin. No further surgical interventions or adjuvant therapies were needed. The patient will have a close follow up. Conclusion: The presence of t(12;15) (p13;q25) translocation which results in the ETV6-NTRK3 gene fusion or positive immunochemical studies for STAT5, mammoglobin and S100 protein, are necessary to confirm the diagnosis of MASC. MASC treatment should mimic the management of other low-grade malignant salivary gland neoplasms. The inhibition of ETV6-NTRK3 gene fusion could be used as treatment in the future.